Literacy IT untuk Pengembangan Keterampilan Guru SD dan MI Kota Ternate Menghadapi Era Revolusi Industri 4.0 - Ade Haerullah; Said Hasan; Jailan Sahil (Jurnal Ilmiah Wahana Pendidikan, 2019)
The purpose of this study was to obtain initial information about the perception and knowledge of IT Literacy as well as a profile of the basic knowledge of elementary and MI teachers throughout Ternate about IT literacy. This study uses a survey research method with a quantitative approach. The data collection technique used was by distributing questionnaires and conducting interviews on a predetermined sample of 25 schools and madrasah with a sample of teachers who were determined randomly. The data is calculated based on the number of checklists filled in by the respondents, then a percentage is used to determine the level of perception of each teacher. The results showed that the highest ability of teachers to operate Microsoft Office was in elementary schools located in the central and northern areas of Ternate City, which were 58% and 50% respectively. Meanwhile, the average IT support skills for elementary school teachers have not met the standard, which is <50%. The basic literacy ability of IT teachers is also relatively low, at 56%. The researcher's recommendation is that it is necessary to conduct IT training for elementary school teachers in 4 sub-districts of the city of Ternate, and continuous assistance so that the learning process becomes quality and student learning outcomes are further improved